2021
DOI: 10.21203/rs.3.rs-140421/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reliability of the Freehand Region-of-Interest Method in Quantitative Cerebral Diffusion Tensor Imaging

Abstract: Background: Diffusion tensor imaging (DTI) is a magnetic resonance imaging (MRI) technique used for evaluating changes in the white matter in brain parenchyma. The reliability of quantitative DTI analysis is influenced by several factors, such as the imaging protocol, pre-processing and post-processing methods, and selected diffusion parameters. Of the post-processing methods, the region-of-interest (ROI) method is most widely used because it is found in commercial programs. The focus of our research was to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…All data were processed and analyzed in Horos by one person. Previous analyses of inter-and intra-operator variability in ROI-based measurements, however, revealed no significant differences between measurements [17,37,42]. Fig.…”
Section: Limitationsmentioning
confidence: 76%
“…All data were processed and analyzed in Horos by one person. Previous analyses of inter-and intra-operator variability in ROI-based measurements, however, revealed no significant differences between measurements [17,37,42]. Fig.…”
Section: Limitationsmentioning
confidence: 76%
“…Currently, there are no published studies on ROI delineation methods in nerve root measurement. Wu et al [28] and Wang et al [29] used the multi-point averaging method for the evaluation of the spinal cord and the grading of cervical spondylotic myelopathy, and Zhu et al [25] and Hakulinen et al [26] used the freehand method for the evaluation of cervical spinal cord trauma and brain matter, respectively. These four studies did not examine specifically the nerve roots, and they did not compare different delineation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Four delineation methods were used: 1) freehand method (Fig. 2A): manually tracing the ROI along the nerve root contour to avoid cerebrospinal fluid interference [25,26]; 2) maximum roundness (Fig. 2B): the round ROI was drawn as large as possible, tangential to the edge of the nerve root, covering the maximum nerve root area and not exceeding the edge [27]; 3) quadrilateral method (Fig.…”
Section: Image Processing and Analysismentioning
confidence: 99%
“…To date, consistency of MRI-based WM measurements has been evaluated through numerous studies, especially for the DWI technique (Boekel et al, 2017; Grech-Sollars et al, 2015; Hakulinen et al, 2021; Magnotta et al, 2012; Teipel et al, 2011; Thieleking et al, 2021; Veenith et al, 2013). These studies reported moderate to high reliability in the WM using Intraclass correlation coefficient (ICC) or Pearson’s correlation ranging from 0.5 to >0.8 as well as within- and between-subject coefficients of variation (CV) ranging from 1 to 8% and 1 to 15% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These studies reported moderate to high reliability in the WM using Intraclass correlation coefficient (ICC) or Pearson’s correlation ranging from 0.5 to >0.8 as well as within- and between-subject coefficients of variation (CV) ranging from 1 to 8% and 1 to 15% respectively. Among DTI-derived measures, Fractional anisotropy (FA) and Mean Diffusivity (MD) generally show the highest reliability across different WM regions (Acheson et al, 2017; Hakulinen et al, 2021; Luque Laguna et al, 2020; Palacios et al, 2017; Shahim et al, 2017; Thieleking et al, 2021; Zhou et al, 2018). For NODDI-derived measures, studies reported similar (intracellular volume fraction, ICvf) or higher (orientation dispersion, OD) reliability compared to DTI measures, while isotropic volume fraction (ISOvf) showed the poorest reliability (ICC<0.6) (Andica et al, 2020; Chung et al, 2016; Granberg et al, 2017; Lucignani et al, 2021; Tariq, 2013).…”
Section: Introductionmentioning
confidence: 99%